Access to Agrarian Right Justice: The Study of Indonesian Women Struggle in Transnationality Marriage - Rinawati Prihatiningsih (Yayasan Jurnal Perempuan, 2017)
The paper brings about the personal experience of Indonesian women citizen (WNI) who marry to foreigners (WNA) in obtaining access to their right in land ownership and in struggling to challenge the constrains and strategies in order to have their rights rehabilitated by the state who has been treating the citizen unfairly. The marriage status has caused women to be discriminated if they don’t have a prenuptial agreement. The research uses feminist-perspective qualitative methodology, reinforced by three theories, namely multicultural feminism, feminist legal theory, and access to justice theory. There are three findings of the research. First, the prenuptial agreement places woman WNI in a dilemmatic position to choose between access to land ownership rights or joint marital property. Second, some see this and name it as legal smuggling or some dub it legal breakthrough. Third, it is necessary to build solidarity to unite in struggling for change against discriminative policy, by involving and being involved in voicing woman experience to rehabilitate equality of rights before the law.